MENTAL HEALTH CONDITIONS IN SOCIAL MEDIA ADDICTION - Hidayat, Dede Rahmat; Wulandari, Afifah; Yulianti, Indah Dwi; Febriyanti, Kenny; Fahroni, Nana Agus; Maulida, Siti Aisyah (EDUCATIONE, 2024)
Teenagers are active users of social media, especially Instagram. Based on research conducted by (Sakti &; Yulianto), as many as 59% of online users aged 18-29 years use Instagram. This study aims to explore the mental health conditions of students who are indicated to experience social media addiction where respondents are aged 18-22 years in the Jabodetabek area. Respondents were randomly selected who met the criteria, namely aged 18-22 years and were S-1 students at Jabodetabek University, filled out questionnaires distributed via google form and filled out questionnaires on social media addiction and mental health. Based on the results of the study, out of 50 existing respondents, there were 7 respondents who indicated social media addiction. With an average of 85.04 and a standard deviation of 15.51. Of the 7 respondents who indicated social media addiction, it can be seen that after filling out the instrument (MHI-38), 3 of them have good mental health. This is because the higher the score possessed by respondents in filling the MHI-38 instrument, the better their mental health condition. The results of the study complement previous studies where overall mental health conditions in social media addiction have not been widely studied.